Efektifitas Penerapan Tanggung Jawab Sosial Lingkungan - Nuriyatman, Eko; Fitria, Fitria; Naili Hidayah , Lili; Dwi Arita Deli, Mutia (Fakultas Hukum Universitas Riau, 2025)
Social and Environmental Responsibility is a form of company commitment in supporting sustainable development by considering social, economic, and environmental aspects. As one of the State-Owned Enterprises, it has implemented a pattern as part of a sustainable business strategy. This study aims to analyze the effectiveness of the implementation of social and environmental responsibility carried out by PTPN VI Jambi in economic, environmental, and legal and governance aspects. In the economic aspect, TJSL PTPN VI focuses on improving community welfare through Small and Medium Enterprises empowerment programs and increasing access to education and health. From the environmental side, the company implements policies that are oriented towards sustainability, such as reforestation programs, waste management, and carbon emission reduction. Meanwhile, in the legal and governance aspects, PTPN VI ensures compliance with applicable regulations, transparency in reporting, and strict program evaluation. The results of the analysis show that the TJSL program that has been implemented has had a positive impact on the surrounding community, increased environmental awareness, and strengthened more accountable corporate governance. With transparent reporting and wide accessibility of information, TJSL PTPN VI can be an effective implementation model for other companies in carrying out their social responsibilities.